Technology and analysis of 08Cr9W3Co3VNbCuBN steel large diameter thick wall pipe welding process - Wang Feng; Zhang Fengshou; Ma Jiang; Ma Xizhen (High Temperature Materials and Processes, 2023)
In this article, the welding technology of large diameter thick wall 08Cr9W3Co3VNbCuBN (G115) heat-resistant steel pipes for the main steam pipe of a 650°C ultra-supercritical power station boiler has been investigated, and the mechanical properties and microstructure of welded joints at different wall thickness positions have also been analyzed. The results show that the mechanical properties of narrow gap welded joint of 115 mm thick large diameter 08Cr9W3Co3VNbCuBN heat-resistant steel pipe obtained by Gas tungsten arc welding (GTAW) + shielded metal arc welding (SMAW) + automatic submerged arc welding (SAW) can meet the requirements of relevant standards after tempering at 780°C. The tensile failure of the welded joint occurs in the base metal zone far away from the weld, an obvious necking phenomenon appears at the fracture position, and the welded joint has good tensile properties. No δ ferrite phase was found in the weld and heat-affected zone (HAZ). The microstructures of each zone are tempered martensite.